Assessing Antimicrobial Usage Practices in Commercial Tilapia Farming: A One Health Cross-sectional Survey in Bangladesh - Rheman, Shafiq; Khor, Laura; Hossain, Sabrina; Delamare-Deboutteville, Jerome; Chadag, Vishnumurthy Mohan (WorldFish, 2024)
The objective of the present study is to evaluate the knowledge, attitudes, perceptions, and farming practices concerning AMU within tilapia-dominant polyculture food production systems in Bangladesh. The rationale behind this investigation is rooted in the belief that comprehending the behavior and practices of fish farmers is crucial for conducting experimental tests on the potential impact of reduced reliance on AMU on the production and profitability of fish farming. The study spanned from November 2022 to April 2023 and was conducted in five Upazilas situated in the Mymensingh district of Bangladesh, a region noteworthy for the rapid and substantial growth of commercial finfish farming in ponds, both in terms of scale and variety. During the study period both a retrospective cross-sectional (CS) and longitudinal survey (LS) were conducted to evaluate the knowledge, attitudes, perceptions, and practices, and monitor ongoing farming practices of 120 tilapia farmers